PENGARUH LEVERAGE TERHADAP PENGHINDARAN PAJAK DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI Periode 2020) - Corina, Vania Rika; Wahyuni, Ika; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2022)
The background of this research is because the development of the consumer goods industry sector is one of the pretty interesting industries and consumer goods products are always needed in daily life. The consumer goods industry is one of the most needed industrial sectors, because all consumer goods industrial products are always in demand by the public, especially now that Indonesia is a very large country with a large population. The consumer goods industry sector is one of the business sectors that will continue to experience growth. Along with the increasing population growth and current economic conditions in Indonesia, the demand for this consumer goods industrial sector will continue to increase. This study aimed to analyze and examine the effect of leverage on tax avoidance in consumer goods industrial sector companies through profitability. The sampling technique was carried out by purposive sampling by determining certain criteria. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS - SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Leverage (DAR) has a significant positive effect on Profitability (ROA), Leverage (DAR) has a negative but not significant effect on Tax Avoidance (ETR), and Profitability (ROA) has a significant positive effect against tax avoidance (ETR). The results of the indirect hypothesis test show that the variable Leverage (DAR) on Tax Avoidance (ETR) through Profitability (ROA) has a significant positive effect.